The Analytical Hebrew And Chaldee Lexicon : Every Word And Inflection Of The Hebrew Old Testament Arranged Alphabetically And With Grammatical Analyses. A Complete Series Of Hebrew And Chaldee Paradigms, With Grammatical Remarks And Explanation - Davidson, Benjamin, d. 1871. (Grand Rapids, MI : Zondervan Publishing, 1972)
Originally published in 1848.
Keywords: Hebrew language -- Dictionaries -- English; Hebrew language -- Inflection; Lexicon --Old Testament -- Grammatical analyses